Diallel analysis of Snap bean (Phaseolus vulgaris l.) varieties for important traits - Arunga, Ester E.; Van Rheenen, Henk A.; Owuoche, James Otieno (Academic Journals, 2010)
The breeding programmes of many crops use diallel analyses because of the genetic information they offer to breeders. Six morphological and agronomic traits of Snap bean (Phaseolus vulgaris L.) were studied to investigate their gene action, and to estimate the general combining abilities (GCA) and specific combining abilities (SCA) of parents and crosses. Three snap bean varieties - Amy, Monel and Morlane and two dry bean varieties - GLP 20 and GLPX 92 were used as parents in a complete diallel cross. The experiment was laid out in a randomized complete block design in a greenhouse. Significant (p < 0.01) additive and dominance effects were observed for days to flowering, plant height at flowering, number of pods per plant, pod weight per plant, pod length and pod diameter. Additive gene effects were predominant for all traits apart from pod weight. Significant (p < 0.01) maternal and non-maternal reciprocal effects were detected on plant height and days to flowering. Estimates of GCA, SCA and reciprocal effects suggested that Amy, Morlane and GLP 20 were generally the best combiners for incorporation into snap bean breeding programmes. This basic information is valuable for snap bean breeding programmes.
Keywords: Diallel analysis; snap bean; additive; dominance; GCA; SCA